Photodynamic bubble-generating microneedles for enhanced transdermal cancer therapy - Ning, Xiaoyu (2022)
Active bubble-generating microneedles (MNs) upon skin interstitial fluid (ISF) contact facilitate deeper and more efficient delivery of intradermal therapeutics. However, bubble-generating MN platforms are sensitive to moisture, which limits their variety to load various functional drugs. This article presents a frozen immersion method that facilitates both hydrophobic and hydrophilic drug loading onto bubble-generating MNs without compromising both drug and MN properties. The formed bubbles upon ISF contact induce distinct vortex flow that produces a propulsion force to enhance drug transportation. The efficiency of transdermal drug delivery is further enhanced by sonophoresis. The drug delivery efficiency of this platform is first evaluated ex vivo using fresh mouse skins and human keloid tissues. Later, in the tumor-bearing mouse model, the platform enhances the skin penetration of photosensitizers (i.e., methylene blue) and correspondingly improves the efficacy of photodynamic therapy.